Recent update of therapeutic application of peroral cholangioscopy - Yun Nah Lee (Society of Gastrointestinal Intervention, 2021)
Despite advancements in endoscopic retrograde cholangiopancreatography (ERCP), direct endoscopic visualization of the biliary tree by cholangioscopy is required to improve the diagnosis and treatment of the underlying disease. Although several types of peroral cholangioscopy (POC) systems are available, single-operator cholangioscopy (SOC) has been widely used for interventions in the biliary system. The first SOC was SpyGlass direct visualization system (Boston Scientific, Natick, MA, USA) expanded to a digital version of the SOC (SpyGlass DS; Boston Scientific). More recently, single-operator direct POC using an ultra-slim upper endoscope has been proposed. The remarkable developments in POC and available specialized accessories continue to improve therapeutic procedure of the biliary diseases. POC allows the visualization of bile duct stone and guide wire placement across difficult strictures and selective cannulation of the intrahepatic and cystic ducts. It is also demonstrating its utility in investigational applications such as intraductal ablation therapy for bile duct tumors, removal of foreign body in the bile duct and evaluation of hemobilia.